Augmenting EFL Students’ Vocabulary Mastery Using Cake Application - Klarida Viany De Berthania Viany; Madar Aleksius; Yohanis Nurak Siwa (Journal of English Language and Education, 2026)
Vocabulary mastery is a foundational component of English foreign language (EFL) acquisition, yet students frequently struggle with retention, pronunciation, and contextual application due to conventional, rote-learning methods. This study aimed at investigating the implementation of the Cake Application as a Mobile-Assisted Language Learning (MALL) platform to improve the vocabulary mastery of Grade XII Language and Culture (IBB) students at SMAN 9 Kupang, while identifying the pedagogical benefits and operational challenges encountered during the process. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart cyclical model, this study was conducted across two cycles involving 18 participants. Data collection utilized instrument triangulation, integrating quantitative pre-tests and post-tests with qualitative observation sheets, field notes, and semi-structured interviews. The quantitative baseline results from the pre-test indicated low initial lexical proficiency with a class mean score of 43.88, which was below the school's Minimum Mastery Criteria (KKM) of 75. Following the integration of Cake's multimedia short videos and interactive drills, the class mean score advanced to 70.00 in Cycle I, though lingering deficits in spelling and context remained. Refined pedagogical scaffolding and focused spelling tasks in Cycle II successfully propelled the final class mean score to 87.22, with all success criteria fully satisfied. Qualitative findings revealed that despite minor infrastructure-related challenges like network instability and ambient noise, students developed independent error-correction habits and high learning autonomy. In conclusion, the integration of the Cake Application effectively bridges lexical gaps, enhances cognitive retention through visual-auditory input, and establishes a highly motivating, self-directed learning environment for EFL learners.